Oxidative Stress and the Role of NADPH Oxidase in Glaucoma - Jennifer C. Fan Gaskin; Manisha H. Shah; Elsa C. Chan (MDPI AG, 2021)
Glaucoma is characterised by loss of retinal ganglion cells, and their axons and many pathophysiological processes are postulated to be involved. It is increasingly understood that not one pathway underlies glaucoma aetiology, but rather they occur as a continuum that ultimately results in the apoptosis of retinal ganglion cells. Oxidative stress is recognised as an important mechanism of cell death in many neurodegenerative diseases, including glaucoma. NADPH oxidase (NOX) are enzymes that are widely expressed in vascular and non-vascular cells, and they are unique in that they primarily produce reactive oxygen species (ROS). There is mounting evidence that NOX are an important source of ROS and oxidative stress in glaucoma and other retinal diseases. This review aims to provide a perspective on the complex role of oxidative stress in glaucoma, in particular how NOX expression may influence glaucoma pathogenesis as illustrated by different experimental models of glaucoma and highlights potential therapeutic targets that may offer a novel treatment option to glaucoma patients.